Technology of underwater laying of concrete mortar in the construction of bridge structure foundations (Международный научный журнал «Инженер», 2026)
The article discusses bridges, which are engineering structures designed to lay transport highways over naturaland artificial water obstacles, and the technologies for their underwater construction. In particular, thetechnology of laying concrete mix using the VPT (vertical movable pipe) method, which is one of the importantstages in the underwater construction of bridge foundations, is analyzed. The VPT method allows maintainingthe quality of concrete in an underwater environment, ensuring its hydraulic properties and strength. This methodis widely used in areas where groundwater flows under high pressure, drilled wells, pile foundations, and otherstructures. To prevent the separation and washing away of the concrete mixture, the stability of the waterretention systems and the concrete at the end of the pipe is strictly controlled. The article also extensively coversthe complexity of underwater and surface works, their technological and engineering features